2022
DOI: 10.1155/2022/8561351
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Brain Activity Changes in Patients with Parkinson’s Disease Based on Resting-State Functional Magnetic Resonance Imaging

Abstract: This paper uses resting-state functional magnetic resonance imaging to observe the changes in local consistency of brain activity in patients with Parkinson’s disease (PD). Both healthy volunteers and Parkinson’s disease patients were scanned for resting brain functional imaging, and the collected raw data were processed using resting functional magnetic resonance data processing toolkit software. This study adopted the use of Regional Homogeneity (ReHo). The postprocessing method of RS-fMRI is to study the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…This was consistent with previous findings that the degeneration of brain neurons in PD patients led to extensive cortical thickness thinning of the cerebral cortex (Laansma et al, 2021;Sarasso et al, 2021), such as the temporal, frontal, and parietal regions (Tang et al, 2021;Zhang et al, 2014). In addition, previous studies found that PD patients had a significantly higher Regional Homogeneity (ReHo) value in the precentral regions compared with HC group, which might be related to cognitive and behavioral dysfunction of PD patients (Shen & Xu, 2022). Bankssts was found to be associated with the lateralization of motor symptoms, and might play a key role in right-onset of PD (Zhang et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…This was consistent with previous findings that the degeneration of brain neurons in PD patients led to extensive cortical thickness thinning of the cerebral cortex (Laansma et al, 2021;Sarasso et al, 2021), such as the temporal, frontal, and parietal regions (Tang et al, 2021;Zhang et al, 2014). In addition, previous studies found that PD patients had a significantly higher Regional Homogeneity (ReHo) value in the precentral regions compared with HC group, which might be related to cognitive and behavioral dysfunction of PD patients (Shen & Xu, 2022). Bankssts was found to be associated with the lateralization of motor symptoms, and might play a key role in right-onset of PD (Zhang et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…This was consistent with previous findings that the degeneration of brain neurons in PD patients led to extensive cortical thickness thinning of the cerebral cortex 6,13 , such as the temporal, frontal, and parietal regions 14,23 . In addition, previous studies found that PD patients had a significantly higher Regional Homogeneity (ReHo) value in the precentral regions compared with HC group, which might be related to cognitive and behavioral dysfunction of PD patients 24 . Bankssts was found to be associated with the lateralization of motor symptoms, and might play a key role in right-onset of PD 25 .…”
Section: Discussionmentioning
confidence: 95%
“…They provide new avenues for studying functional and structural connectivity, mapping brain networks, decoding cognitive processes, and identifying neurological disease biomarkers. Studying neurological disorders: fMRI is often used to study changes in brain function associated with neurological disorders such as AD, PD, schizophrenia, and depression [17,18]. This can provide insights into the underlying mechanisms of these disorders and help with diagnosis and treatment.…”
Section: Applications Of Fmri In Studying Brain Functionmentioning
confidence: 99%